The Development of a Violinistic Idiom in Early Violin Music: Violin Music and its Composers in the Early 17th Century in Italy - Cook, Shannon (College of Music, 2023)
The objective of this study is to trace the emergence, development, and use of violinistic idioms within written violin music in Italy from the end of the 16th century to the mid-17th century. The aim of this study is to render a concise and integrated narrative of how the Italian violinist composers in early and middle 17th century created, developed, and used violinistic idioms within violin music. This study's time frame starts with the emergence and early development of instrumental and early violinistic idioms during the end of the 16th century. The time frame concludes with the middle decades of the 17th century when the first ‘violin virtuosi' in the Mantuan violin school – the first ‘violin school' – displayed far more advanced and specific violinistic idioms within their violin music. The study has two elements: A historical aspect and an analytical aspect. The historical aspect discusses the historical and musical aspects of the development of violinistic idioms within violin music at the time. In the analytical aspect of the study, musical examples from the works of the pertinent violinist composers are discussed in order to exam how violinistic idioms were utilised and development within their violin works. The study reaches the conclusion that: the early 17th century was an active period in the history of the development of violinistic idioms within violin music. Within a matter of decades, the violin grew from being one of various accompaniment instruments in the late 16th century to being the most popular treble instrument for musical expression, that even rivalled the voice by the middle decades of the 17th century. Throughout the early 17th century, the observable trend was that of an idiomatic development which lent itself to the pursuit of virtuosity and technical display. By the middle of the 17th century, a more advanced and complex awareness of the violin's capabilities allowed violinist composers to expand virtuosity, technicality, and expression within violin music. This expansion – especially observable through the violin music of the Mantuan violinist composers – formed the foundation for the transformation of development within violin music towards the late 17th century and onwards.